Analisis Ketebalan Lapisan pada Pengecatan Baja Karbon Rendah menggunakan Metode Respons Permukaan - Hayun Indra Nur Iman; Mahros Darsin; Rahma Rei Sakura (University of Muhammadiyah Jakarta, 2019)
The number of vehicles has increased every year. This increase was accompanied by an increase in the number of accidents that occurred. Accidents that occur result in damage to vehicles so that repainting is needed. Painting is an effort made by applying paint in liquid form on the surface of an object to create a layer on the surface of the object. Painting serves to protect and improve the appearance of a surface. The purpose of this study is to determine the effect of a combination of parameters that can produce maximum thickness values. The experimental design used in this study is a surface response method with three parameters where each parameter has three levels. The parameters chosen were spraying distance (110 mm, 130 mm, 150 mm), composition between paint-thinner (1: 1.6; 1: 1.4; 1: 1,2), and pressure (3,5; 4 , 5; 5.5). The painting process is carried out with the help of a paint test demonstrator. The painting results are dried in the oven and then measured using a thickness gauge. The measurement data is processed using the help of Minitab software and the estimator equation for thickness is obtained. The parameters with the greatest influence in this study are the distance of spraying with a distance coefficient of 2.258. Painting with the highest average value of thickness occurred in the fifteenth experiment with a thickness value of 39.9µm. The thickness is obtained by variable variations of 130mm distance, paint-thinner 1: 1.4 composition and 4.5 bar pressure.